Chiral Fidelity in the Diastereoselective and Enantiospecific Synthesis of Indenes from Axially Chiral Benzylidene Cyclanes. Issue 35 (1st June 2017) - Mouysset, Dominique; Tessonnier, Cyril; Tintaru, Aura; Dumur, Frédéric; Jean, Marion; Vanthuyne, Nicolas; Bertrand, Michèle P.; Siri, Didier; Nechab, Malek
Abstract: Enantioenriched indenes were reached through a chirality conversion strategy using original axially chiral benzylidene cyclanes. Good to high remote diastereocontrol and excellent enantiocontrol were observed in this cascade involving copper‐catalyzed homologation of terminal alkynes, in situ allenoate formation and Alder‐ene cyclization. Abstract : Fidelity is a virtue ! The enantiospecific conversion of axially chiral benzylidene cyclanes to indenes possessing central chirality proceeds with high chiral fidelity in an Alder‐ene cyclization.